(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article analyzes the phenomenon of youth slang as a significant sociolinguistic phenomenon that profoundly influences the culture of contemporary society’s speech. It examines the primary functions of slang expressions, their origins, and the ways they spread and become established in language. Special attention is given to the dual role of slang: on one hand, it serves as a means of selfexpression and innovation, while on the other, it can have a destructive impact on speech culture. The paper also addresses the issues of slang’s interaction with literary norms and its role in the era of digital communication.